Kinematical Model of Currency Dynamics - Boyarshinov, Boris; Yuzhakova, Nina (Journal of Reviews on Global Economics, 2018)
The work is devoted to the actual topic of forecasting of sharp changes in exchange rates. The paper uses the analytical approximation of data on the dynamics of the USD and EUR currency pair, based on the physical model. The paper shows signs of an approaching sharp change in the exchange rate of a currency pair.